Higher Genetically Predicted Triglycerides, LDL, and HDL Increase the Vitamin D Deficiency: A Mendelian Randomization Study - Lu, Zhe; Jiao, Yang; Li, Jun (Frontiers in Nutrition, 2022)
Introduction It has been proven that high body mass index (BMI) levels can cause vitamin D deficiency, but the mechanism is still unclear. Therefore, this study attempts to explain this phenomenon from the perspective of blood lipid by using mendelian randomization (MR). Methods Genome-wide association studies (GWAS) summary datasets for serum lipids were obtained from the Global Lipids Genetics Consortium (GLGC). Vitamin D deficiency outcome data were acquired from the UK Biobank samples. Single-variable MR (SVMR) and multi-variable MR (MVMR) analyses were conducted using the TwoSampleMR package based on R 4.0.3. The four main methods were the random-effect inverse-variance weighted (IVW), MR-Egger, weighted-median method, and weighted mode. Results In the SVMR of serum lipid/apolipoprotein levels on serum vitamin D level, it was found that elevated serum triacylglycerol (IVW, OR = 0.85, 95%CI:0.81–0.89, P < 0.001), low-density lipoprotein (LDL) (IVW, OR = 0.93, 95%CI:0.90–0.95, P < 0.001), and high-density lipoprotein (HDL) (IVW, OR = 0.95, 95%CI:0.91–0.98, P < 0.001) levels all had a causal relationship with vitamin D deficiency, but significant pleiotropy was detected in the triacylglycerol (P = 0.001) and HDL (P = 0.003) analysis. MVMR analysis results were consistent with SVMR. Conclusion By using single-variable mendelian randomization and multi-variable mendelian randomization methods, we identified that the elevated serum triacylglycerol, LDL, and HDL levels all had a causal relationship with vitamin D deficiency. Taking into account the significant pleiotropy demonstrated in this study, the conclusions of this study should be treated with caution.